An assessment and forecast highlighting the importance of restructuring and integration in cross-border acquisitions in Poland: An analysis of M&A experts' opinions - Witold Nowinski (Journal for East European Management Studies, 2006)
This study analyses the importance of restructuring activities and integration in cross-border acquisitions of Polish firms. We find that in comparison to acquisitions in developed economies analogous transactions in Poland are characterized by the particularly high role of retrenchment, positive impact of changes among incumbent managers and the relatively lower role of integration depth. Evidence concerning possible changes of these factors in the future is not unambiguous. Nonetheless, our findings indicate the possibility of their transition as well as its direction. Potential changes are expected to go in the direction of reducing the role of restructuring and increasing the role of integration. – – Die Studie analysiert die Wichtigkeit von Umstrukturierungsmaßnahmen und der Integration in grenzüberschreitenden Akquisitionen von polnischen Firmen. Wir finden heraus, dass im Vergleich zu Akquisitionen in entwickelten Ländern analoge Transaktionen in Polen Faktoren wie die Einsparung, der positiven Effekt des Auswechselns von amtierenden Managern und die relative schwache Rolle der Integrationstiefe eine große Rolle spielen. Nachweise über mögliche Veränderungen dieser Faktoren in der Zukunft sind nicht mehrdeutig. Nichtsdestotrotz zeigen unsere Ergebnise die Möglichkeit dieser Transition und auch die einzuschlagende Richtung. Potenzielle Änderungen werden in Richtung von der Reduzierung der Rolle der Umstrukturierung und des Verstärkens der Rolle der Integration abzielen.
Keywords: 650; Cross-border acquisitions; Poland; Restructuring; Integration; Privatisation